As igrejas menores nas quebradas de fé: a construção da hegemonia do pentecostalismo nas periferias de São Paulo (1990-2010) - Marques, Vagner Aparecido (2019)
The Brazilian religious field has been undergoing important transformations in the last decades, with the decline of Catholicism and the continuing rise of the evangelicals that constitute a porous, plural and dynamic group. The Pentecostals make up the overwhelming majority of this group. The 2010 demographic census data revealed that evangelicals jumped from 15% to 22%, while Catholics declined from 73.9% to 64.6%. This study analyzes the process of fragmentation within the evangelical field, responsible for the construction of the hegemony of Pentecostalism in the small churches of the “quebradas da fé”. The religious universe of the municipality of Ferraz de Vasconcelos, the periphery of São Paulo, was chosen as a research field for conducting ethnographies, participant observation, and interviews. In the field research, the general characteristics of the small churches were observed: modest facilities, organized in small family centers, many without legal institutionality and dependent on the personal charisma of its leader. The “quebradas da fé” are the peripheries of São Paulo that have processed significant transformations in the last decades. Mixed and all together, the small churches and the “quebradas de fé” watched in the decade of 1990, on the one hand, the evangelical boom and, on the other, the daily life of war in the outskirts of São Paulo. In 2000, the evangelicals strengthened their growth, while in the peripheries there is the arrival of the PCC, its morality and magical formula of peace, in some cases with agreements and a lot of talks and in others with the war for peace. In 2010 Pentecostalism is fragmented and the small churches are hegemonic in the “quebradas de fé”. In this sense, the Pentecostalism of the small churches reveals itself more than an expression of faith, it is a way of being in the world, configures the ethos of the community, and it is lived in the everyday life of the peripheries of urban centers as a lifestyle